(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: The aim of this study was to detect the existence of developments in resistance to biocide ofPseudomonas aeruginosa resist of colistin and in multi-drug resistance Klebsiella pneumonia in the hospitalenvironment. Materials and Methods: The study included 25 isolates of K. pneumoniae and 30 isolates ofP. aeruginosa. Isolated from different clinical and environmental samples in Baghdad hospitals. Antibioticsensitivity tests and their susceptibility to multiple antibiotic resistance and sensitivity tests were studied forthe most commonly used antiseptics at the preventive level (benzalkonium chloride). The test was carriedout using the micro dilution broth method, following Institution of Clinical and Laboratory Standardsguidelines, PCR was performed for detection of blaTEM, blaSHV , blaCTX-M , qacC/D, qac?E1and qacE betalactamase and antiseptic genes. Results: A high rate of multiple resistance to the most used antibioticswas observed, so the rate of resistance to all antibiotics that was used was 16.0% of P. aeruginosa and 4%of K. pneumoniae possesses comprehensive resistance to all antibiotics that were used and the resiste ofcolistin in P. aeruginosa was 36% .The prevalence of ESBLs was 36.0% and 48.0 % of P.aeruginosa andK.penomoniea respectively ,in addition to their strong ability to form biofilms 80 % in P.aeruginosa and94% in k.pneumoniea and their ability to resist Antiseptics . The percentage of resistance to antiseptic ofbenzilkonium chloride showed the highest concentration of P.aeruginosa was 33.3% and K. pneumoniae37.5% . The result of ESBL and antiseptic genes detection clarify, the percent of production genes were(10%), (40%) blaTEM; (6.66%),(56%)blaSHV ;(33%),(64%) blaCTX-M ;(70%),(44%) qacC/D; ( 80% ),(56%)qac?E1 in P.aeruginosa and K.pneumoniea respectively and no any isolate carried qacE gene. production ofextended spectrum ?-lactamase genes in addition to their strong ability to form biofilms 80 % in p.aeroginosaand 94% in k.pneumoniea and their ability to resist a antiseptics . The percentage of resistance to antisepticof benzilkonium chloride showed the highest concentration of P. aeruginosa was 33.3% and K. pneumoniae37.5%, the result of beta lactamase and antiseptic genes detection clarify PCR was performed for detectionof blaTEM, blaSHV , blaCTX-M , qacC/D, qac?E1and qacE beta lactamase and antiseptic genes . Conclusion:Our observations indicate that there is a significant correlation between the ability of bacteria to resistmultiple antibiotics in addition to their ability to resist the most commonly used antiseptics, due to theirphysiological nature and increased virulence factors.